High levels of plasma fibrinogen are related to post‐stroke cognitive impairment - Liu, Yuntao (Brain Behav, 2019)
INTRODUCTION: Studies have shown that high levels of the fibrinogen (FIB) are related to cognitive deficits. However, the relationship between fibrinogen and cognitive deficit after stroke remains unclear. Therefore, we explored the relationship between plasma fibrinogen and post‐stroke cognitive impairment (PSCI). METHODS: This study is carried out in the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang Province, China. A total of 210 patients with acute ischemic stroke were enrolled in this study. Ultimately, 134 patients completed 3‐month follow‐up. Blood samples were collected at hospital admission. Cognitive function was evaluated 3 months after stroke. All patients underwent the Mini‐Mental State Examination (MMSE) after 3 months. RESULTS: Higher levels of fibrinogen were observed in patients with post‐stroke cognitive impairment compared with the non‐PSCI group (p < .001). Additionally, elevated plasma fibrinogen levels were independently associated with PSCI (odds ratio [OR] = 2.000, 95% CI 1.062–3.770 p = .032). The plasma fibrinogen levels were negatively correlated with the 3‐month MMSE scores (r = −.171, p = .048). In a multivariate linear regression, FIB was negatively associated with the 3‐month MMSE scores after adjustment for the other variables (β = −0.782, p = .035). CONCLUSION: High levels of plasma fibrinogen were associated with the presence and severity of PSCI.